A feasible strategy for self-assembly of gold nanoparticles via dithiol-PEG for photothermal therapy of cancers. Issue 11 (7th February 2018) - Fu, Yingjie; Feng, Qishuai; Shen, Yajing; Chen, Mengwei; Xu, Chang; Cheng, Yu; Zhou, Xiang
Abstract : We designed and explored self-assembled gold nanoparticles (SAGNPs) by introducing dithiol modified polyethylene glycol (PEG) for internanoparticle cross-linking. Abstract : We designed and explored self-assembled gold nanoparticles (SAGNPs) by introducing dithiol modified polyethylene glycol (PEG) for internanoparticle cross-linking. SAGNPs could enhance uptake into cancer cells and be disintegrated by glutathione (GSH) to achieve tumor microenvironment-activated biodegradation. This assembled structure improved the photothermal effect compared to single gold nanospheres.